Imprinting disorders: a group of congenital disorders with overlapping patterns of molecular changes affecting imprinted loci. Issue 1 (December 2015) - Eggermann, Thomas; Perez de Nanclares, Guiomar; Maher, Eamonn; Temple, I.; Tümer, Zeynep; Monk, David; Mackay, Deborah; Grønskov, Karen; Riccio, Andrea; Linglart, Agnès; Netchine, Irène
Abstract Congenital imprinting disorders (IDs) are characterised by molecular changes affecting imprinted chromosomal regions and genes, i.e. genes that are expressed in a parent-of-origin specific manner. Recent years have seen a great expansion in the range of alterations in regulation, dosage or DNA sequence shown to disturb imprinted gene expression, and the correspondingly broad range of resultant clinical syndromes. At the same time, however, it has become clear that this diversity of IDs has common underlying principles, not only in shared molecular mechanisms, but also in interrelated clinical impacts upon growth, development and metabolism. Thus, detailed and systematic analysis of IDs can not only identify unifying principles of molecular epigenetics in health and disease, but also support personalisation of diagnosis and management for individual patients and families.